Comparison of the performance of Nigerian indigenous chickens from three agro-ecological zones - Adetayo, A.S.; Babafunso, S. E. (2001)
Nigerian indigenous chicken (NIC) from three agro-ecological zones (Rain Forest, RF; Derived Savanna, DS; and Guinea Savanna, GS) were evaluated for age at first egg, egg production and egg weight, percent hen-day egg production and percent laying mortality. Data for this work were collected over a period of 72 weeks. A total of 579 eggs from DS and RF zones and 505 growers from DS, GS and RF were evaluated. Data were compiled by Dbase IV and analysed using the General Linear Model (GLM) procedure of Statistical Analysis System (SAS). Agro-ecological zones, age and sex were the fixed effects in the model. Means for each variable effect were compared using the Least-Square Analysis of Variance and Duncan option of SAS. For all the traits evaluated, there was no significant difference between the chickens from the three ecological zones. Hence, the Nigerian indigenous chickens from these zones cannot be said to belong to different genetic groups.